The Biography of Zbigniew Anthony Kruszewski. A Report on a Book-Tour in the USA - Halicka, Beata (Sensus Historiae, 2021)
The report concerns a series of presentations of the monograph entitled Borderlands Biography: Z. Anthony Kruszewski in Wartime Europe and Postwar America in the United States, which took place in November and December 2021. The purpose of the report is not so much to describe particularthe various stages of the book-tour, but rather to reflect the most important threads ofdiscussions that took place during these meetings. It seeks also to answer the question of why it is worth promoting books.? In addition, the author shares her thoughts on meetings with readers in Germany and other European countries as well asnd on the role of being an “ambassador” of Polish culture abroad.